The Effect Of Intrinsic Motivation, Problem Solving Creativity And Competence On Employee Work Performance Of Bank Jatim Kc Jombang (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This think about points to decide inborn inspiration, problem-solving imagination and competence influence the work execution of Bank Jatim KC Jombang representatives. The think about employments an illustrative investigate strategy that's carried out through data collection within the field. The populace and test of this think about were all Bank Jatim KC Jombang workers totaling 32 representatives, information examination utilizing numerous straight relapse factual strategies and theory testing and coefficient end. Based on the comes about of the study, it appears that work inspiration incorporates a commitment to the work execution of Bank Jatim KC Jombang representatives. Hence, it can be seen that the way better the inherent inspiration, problem-solving inventiveness and great competence, the more it'll progress the work execution of Bank Jatim KC Jombang representatives.
Keywords: intrinsic motivation, creativity, competence and work performance